X-ray absorption spectroscopy study of the electronic structure and local coordination of 1st row transition metal-promoted Chevrel-phase sulfides. Issue 8 (18th April 2019) - Perryman, Joseph T.; Hyler, Forrest P.; Ortiz-Rodríguez, Jessica C.; Mehta, Apurva; Kulkarni, Ambarish R.; Velázquez, Jesús M.
Abstract: The electronic structures of S and Mo as well as the local coordination of Mo are investigated as a function of metal promotion Chevrel-phase (CP) sulfides. We observe the effect of metal promoter-induced electron donation into the stoichiometric range M x Mo6 S8 (M = Fe, Ni, Cu; x  = 0–2) through analysis of X-ray absorption near-edge structure regions. We further observe the effect of this promotion on the bonding environment of Mo6 metal centers through extended X-ray absorption fine structure analysis. We monitor expansion and contraction of Mo6 octahedra with and without metal promotion, as has been predicted by Hückel molecular orbital theory. We further observe a marked tunability in the electronic structure of sulfur upon charge transfer between promoting species and Mo6 S8 units. Average Mo6 octahedron Mo–Mo bond contraction from 2.76 Å to as short as 2.69 Å was observed upon incorporation of metal promoters, while intercluster separation displays a pronounced increase for promoter-host lattices compared to un-promoted Mo6 S8 . To corroborate spectroscopically observed phenomena, we performed computational analyses of spin-polarized densities of state for the CP materials investigated herein, where a detectable increase in sulfur-based frontier orbital population is observed in accordance with experimentally validated orbital filling. Graphical abstract: